Albania : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for a Waiver of Nonobservance of Performance Criterion, and Financing Assurances Review. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper focuses on Albania's Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), Request for a Waiver of Nonobservance of Performance Criterion, and Financing Assurances Review. Performance since the third review has been satisfactory overall, although 2003 fiscal revenue fell short of the ambitious budget targets. All quantitative performance criteria for end-March 2004 were met. The end-December 2003 indicative target for net credit to government was also met substantially despite revenue and external assistance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet